Representations of Nature in Human Culture - da Silva, Wellington Amâncio (American Journal of Human Ecology, 2014)
This article aims to give a brief historical survey of the representations of the relationship between nature and human culture. These representations are conditioned to view philosophical and scientific world taking into account the positivist aspects of this vision, present since the Greek and Roman civilization. The idea that man submits himself to the environment as a way of maintaining their survival has no sustainable moral and ethical grounds when compared to current degradation of nature, proving that science and philosophy took little or no account of the issue of otherness. Therefore the construction of human culture, ie Western civilization under the aspects of rationalism has always been the factor of environmental destruction inherent in this same rationalism. We believe that with a paradigm shift that has been presented, we can start our relationship with nature.